Factors associated with work engagement of nurses in the radiology department, Japan: a cross-sectional study - Tsuchihashi,Hitomi; Yamaguchi,Takumi; Yamada,Yumiko; Koyama,Tamami; Matsunari,Yuko (PeerJ, 2024)
Background Radiology departments present unique challenges compared to other departments due to exposure to radiation and the specialized nature of the work. Nurses must not only manage typical nursing duties but also adhere to strict safety protocols to minimize radiation exposure. These additional responsibilities can significantly impact their work engagement and overall job satisfaction. Objective This study aimed to identify the factors associated with work engagement among nurses working at prefectural designated cancer care hospitals in Japan. Identifying these factors may lead to improvements in future work environments and educational systems. Methods This was a cross-sectional study using an internet-based survey. A questionnaire using the Utrecht Work Engagement Scale (UWES) was conducted among 317 nurses; 140 responded (response rate: 44.2%). Results Significant associations were found between work engagement and several factors. The mean UWES score was 54.3 (Standard deviation (SD): 18.4). Work engagement was positively associated with age (B = 0.179, p = 0.03), being male (B = 0.19, p = 0.015), higher position (B = 0.199, p = 0.012), desire for radiology assignments (B = 0.223, p = 0.003), and presence of a radiation exposure consultation system (B = 0.214, p = 0.034). Conclusions This study identified several factors associated with work engagement among radiology nurses, highlighting the importance of specialized support systems to address radiation-related concerns. These findings can inform interventions to enhance work engagement and well-being in this field.
Keywords: Certified nurse specialists; Occupational radiation exposure; Radiology department; Utrecht Work Engagement Scale (UWES); Work engagement